LITERATUR RIVIEW ANALISIS FAKTOR RISIKO TB PARU DI INDONESIA - AINA NURHALIZA; fa Ayu Hamimah; Maghitsa Ayu Herawati; Rieko Alysa Syahputra; Dwi Sarwani Sri Rejeki (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2023)
Background: The incidence of pulmonary tuberculosis (pulmonary TB) increases every year in Indonesia. Various supporting risk factors influence the increase in the number of the diseases. Risk factor analysis needs to do to find out the kind of risk factors that can increase the incidence of pulmonary tuberculosis in Indonesia Objectives: This research is qualified to analyze various factors that risk increasing the incidence of pulmonary TB in Indonesia. Research Metodes: 2015-2023 Literature Study in English and Indonesian. Data were obtained from databases including ScienceDirect, PubMed, ResearchGate, and Google Scholar with keywords Risk factors for pulmonary tuberculosis, tuberculosis in Indonesia, and tuberculosis. Results: Obtained 15 articles according to the topic of the risk factor of pulmonary TB in Indonesia caused by several dominating factors such as the environment including ventilation, temperature, and type of floor, male is riskier than female, distance and accessibility of health services and latest education. Conclusion: Physical environment, gender, accessibility in health service facilities, and the latest education is the main risk factor that causes high morbidity due to pulmonary TB in Indonesia. Keywords: Risk Factor; Pulmonary Tuberculosis; Indonesia